Potency of anti-trematode in inhibiting cathepsin-2L and cathepsin-5L of Fasciola gigantica using homology, docking, and molecular dynamics - Henni Vanda; Farida Athaillah; Wahyu Eka Sari; Frengki Frengki; Nurliana Nurliana; Muhammad Hambal (Open Veterinary Journal, 2024)
Background: Cathepsin-L (FhCL) is a group of enzymes that most flukes express and secreted significantly in parasite-host interactions. Researches are focusing on antigens released by Fasciola gigantica as one of the keys for understanding immunologic pathway in parasite infection and targets for anthelmintics. Efforts to suppress FhCL function through vaccination or therapy using anthelmintic drugs are key factors in controlling field level trematode infections. A molecular docking method can be used to observe the interaction between FhCL and some anthelmintic drugs to better understand the effect of these anthelmintics on FhCL. Furthermore, it is necessary to carry out molecular dynamics method to observe the dynamic pattern of the interaction of the enzyme-ligand when the dynamics simulation is in progress.